Ex situ conservation of rare and endangered species in mushroom culture collections of Ukraine - Bisko, N.A.; Sukhomlyn, M.M.; Mykchaylova, O.B.; Lomberg, M.L.; Tsvyd, N.V.; Petrichuk, Yu.V.; Al-Maali, G.A.; Mytropolska, N.Yu. (Український ботанічний журнал, 2018)
Biodiversity loss, degradation of ecosystems and other global concerns emphasize urgent issues in nature conservation. Fungi as an important component of biodiversity need to be protected as much as other living organisms. In the article, two basic strategies in conservation are outlined and recent advances in fungal conservation, both in situ and ex situ, are considered. The key role of mushroom culture collections for ex situ fungal conservation is highlighted. Conservation of species diversity and genetic resources in culture collections provides the essential basis for biotechnological potential. The largest collections of fungi registered in the World Data Center for Microorganisms (WDCM), a unique global network for ex situ preservation of fungal and microbial diversity, are mentioned. Of the existing culture collections of fungi in Ukraine, the IBK and FCKU mushroom culture collections are characterized. A list of the species maintained in the IBK and FCKU collections, evaluated in the European countries against the IUCN criteria and categories and available at the European Council for Conservation of Fungi (ECCF) website as the preliminary European Red List of endangered macrofungi, is provided. A special attention paid in the IBK and FCKU collections to cultures of rare species of fungi, particularly of those listed in the Red Data Book of Ukraine, as well as the opportunity of the reintroduction into natural habitats are briefly discussed. Some examples of other rare species of fungi from these collections, potential candidates for national red-listing, are presented.